2017
DOI: 10.1016/s0140-6736(16)31589-6
|View full text |Cite
|
Sign up to set email alerts
|

The Healthy Activity Program (HAP), a lay counsellor-delivered brief psychological treatment for severe depression, in primary care in India: a randomised controlled trial

Abstract: SummaryBackgroundAlthough structured psychological treatments are recommended as first-line interventions for depression, only a small fraction of people globally receive these treatments because of poor access in routine primary care. We assessed the effectiveness and cost-effectiveness of a brief psychological treatment (Healthy Activity Program [HAP]) for delivery by lay counsellors to patients with moderately severe to severe depression in primary health-care settings.MethodsIn this randomised controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
381
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 350 publications
(389 citation statements)
references
References 37 publications
7
381
0
1
Order By: Relevance
“…Another strength was that intensive assessments were not done at baseline as assessment reactivity has been found to be problematic in alcohol use disorder trials 47, 48. Considered together with the companion study, 17 the two PREMIUM trials represent a substantial achievement in global mental health for several reasons. First, the interventions are brief, delivered by lay people and provided to primary health-care attenders with few exclusion criteria, thus enhancing their generalisability to routine health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strength was that intensive assessments were not done at baseline as assessment reactivity has been found to be problematic in alcohol use disorder trials 47, 48. Considered together with the companion study, 17 the two PREMIUM trials represent a substantial achievement in global mental health for several reasons. First, the interventions are brief, delivered by lay people and provided to primary health-care attenders with few exclusion criteria, thus enhancing their generalisability to routine health care.…”
Section: Discussionmentioning
confidence: 99%
“…In this Article, we describe the results of a trial assessing the effectiveness and cost-effectiveness of the CAP treatment when used in primary care. The study of HAP treatment is reported separately 17 . The two trials of HAP and CAP were done concurrently in the same primary health centres (PHCs) and over the same period of time, with the same counsellors delivering both treatments according to the trial allocations of participants.…”
Section: Introductionmentioning
confidence: 99%
“…An RCT in India (Patel et al, 2010) showed that a collaborative care intervention led by lay counsellors was cost-saving to the health system (Buttorff et al, 2012). A 6–8 session behavioral activation treatment delivered by lay counsellors in primary health care settings in India was also cost effective, reducing depression and improving functioning in people with moderately severe to severe depression (Patel et al, 2017; Weobong et al, 2017). A systematic review of task-shifting interventions for non-communicable diseases in LMICs showed that it is potentially effective for improving access for mental healthcare (Joshi et al, 2014).…”
Section: Scaling-up Mental Health Interventions For Refugeesmentioning
confidence: 99%
“…Solutions that bring the latest science from research to care will require new partnership models where stakeholders work on a more open agenda even in the early stage process of development [10] and greater sharing of information [11,12,13]. Approaches to integrate early stage research and pragmatic research aiming to improve effectiveness and public health values are being proposed [14,15].…”
Section: Methodsology and Alignment Of Competencies: An Opportunity Nomentioning
confidence: 99%